Calmodulin promotes a Ca2+‐dependent conformational change in the C‐terminal regulatory domain of CaV1.2. Issue 22 (8th November 2022) - Yadav, Deepak Kumar; Anderson, David E.; Hell, Johannes W.; Ames, James B.
Abstract : Calmodulin (CaM) binds to the membrane‐proximal cytosolic C‐terminal domain of CaV 1.2 (residues 1520–1669, CT(1520–1669)) and causes Ca 2+ ‐induced conformational changes that promote Ca 2+ ‐dependent channel inactivation (CDI). We report biophysical studies that probe the structural interaction between CT(1520–1669) and CaM. The recombinantly expressed CT(1520–1669) is insoluble, but can be solubilized in the presence of Ca 2+ ‐saturated CaM (Ca4 /CaM), but not in the presence of Ca 2+ ‐free CaM (apoCaM). We show that half‐calcified CaM (Ca2 /CaM12 ) forms a complex with CT(1520–1669) that is less soluble than CT(1520–1669) bound to Ca4 /CaM. The NMR spectrum of CT(1520–1669) reveals spectral differences caused by the binding of Ca2 /CaM12 versus Ca4 /CaM, suggesting that the binding of Ca 2+ to the CaM N‐lobe may induce a conformational change in CT(1520–1669). Abstract : Here, we report binding of calmodulin (CaM) to the C‐terminal domain of CaV 1.2 (CT(1520–1669)) to probe conformational changes that regulate channel function. The refolding of CT(1520–1669) in the presence of Ca 2+ ‐saturated CaM forms a soluble complex. The same refolding in the presence of apoCaM does not form a complex, consistent with a lack of apoCaM binding to CaV 1.2.